Draft Sixth Five Year Plan (1978-79 to 1982-83) for Economic Advice and Statistics - Planning Commission (Planning Commission, 1978)
Social Statistics and strengthening of economic analysis unit. The State Government has also directed that a scheme for improvement of Agricultural Statistics limit basic, transferred to the Department should be included in the Sixth Plan.
Department of Statistics, Government of Manipur